Development and assessment of reliability for a sandbag throw conditioning test for wrestlers - Wright, G. A.; Isaacson, M. I.; Malecek, D. J.; Steffen, J. P. (The Journal of Strength and Conditioning Research, 2015)
The purpose of this study was to develop and analyze a sport-specific conditioning test for wrestling that will incorporate the physiological demands of a match. Sixteen D-III collegiate wrestlers performed 2 tests to assess physical conditioning. The developed test (sandbag test) used a bag filled with sand that was repeatedly thrown over a course of seven 1-minute rounds. Average time per throw (T/T) was determined each round. The sandbag test was compared with a previously established repeated sprint protocol of maximal effort arm cranking on an upper body ergometer (UBE). Mean power output was determined for each sprint. Both the UBE test and the sandbag test were compared using performance decrement (%fatigue), blood lactate (BLa), and peak heart rate (HRpeak) values. Test-retest reliability for the sandbag test was found to be almost perfect using T/T (intraclass correlation coefficient, r = 0.96). No significant differences in %fatigue were found between the UBE test and the sandbag test (p = 0.600), BLa (p = 0.283), and HRpeak (p = 0.214). Further analysis by weight class (light-weight class [LWC] and heavy-weight class [HWC]) found a significant interaction for %fatigue between groups for the sandbag test and UBE (p = 0.001), but no interactions were observed for BLa (p = 0.198) or HRpeak (p = 0.990). Although no significant differences were found in %fatigue between the 2 tests when the data were grouped together, a clear difference was found between the LWC and HWC groups only in the sandbag test, indicating that this test may be more sensitive than the UBE. Coaches can assess their wrestlers with this reliable, inexpensive, and time-efficient sandbag test.